Incredible life of Jhalkari Bai: braveheart warrior - Sengupta, Swati (New Delhi: Talking Cub, 2022)
This book talks about Jhalkari Bai incredible and memorable story of bravery and sacrifice.
Keywords: Jhalkari Bai; Biography